Polimorfismos do gene TGF-β1 na pré-eclâmpsia - HORTOLANI, Andrezza Cristina Cancian (2017)
Preeclampsia (PE) is a human pregnancy disorder characterized by hypertension (systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥90 mmHg) and proteinuria (> 300 mg / 24 hours or ≥ 1+ protein detected in the urine-type I test that occurs after 20 weeks of pregnancy. It is responsible for 5 to 8% of the complications that occur during pregnancy, reaching 10 to 18% when compared to underdeveloped countries. Some studies show that the genetic factor is responsible for 50% of PE cases. Transforming Growth Factor Beta-1 (TGF- β1) may contribute to the appearance of clinical signs of PE by influencing inadequate surface placentation, leading to endothelial dysfunction and assisting in the onset of hypertension and proteinuria, which are the most known signs of this pathology. Therefore, this study aims to investigate TGF-β1 gene polymorphisms, positions -509 (C / T) and -800 (G / A), in a Brazilian population, in the region of Uberaba, Minas Gerais. 257 women were included, 88 with PE and 169 from control group. All participants signed the Informed Consent Form (TCLE) and answered an interview about clinical and demographic data. TGF-β1 gene polymorphisms, positions C-509T and G-800A, were investigated by real-time PCR. There was no genotypic association of TGF-β1, C-509T (2= 0.312, p = 0.855) and allelic polymorphism (2= 0.154, p = 0.403) and the development of PE. In the logistic regression analysis, family recurrence was statistically significant, where women who reported a family history of PE had seven times the risk of developing the disease in relation to women with no family history. . It has also been observed that first pregnancy confers an eight-fold risk of developing PE in relation to women who have more than two pregnancies. Therefore, this study suggests that the polymorphisms evaluated do not predispose to the development of PE in this population. Research needs to be done to confirm the data obtained here, as well as large-scale genome studies and functional studies.